Approximation of functions subharmonic in a disk by the logarithm of the modulus of an analytic function - Girnyk, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Yulmukhametov's result concerning the approximation of a function subharmonic in a bounded domain by the logarithm of the modulus of an analytic function is supplemented with an estimate of the exceptional set in the important case of a disk. We show that this approximation is unimprovable in a certain sense.